Filosofía y Feminismo en Celia Amorós - Posada Kubissa, Luisa (Logos. Anales del Seminario de Metafísica, 2010)
The views of Celia Amorós, which are dealt with here, originate in the ideas which appeared, especially in the Enlightenment, and which demanded equality for women. Following this line of thought she studies some of the most powerful theories of Western philosophical tradition in order to carry out a critical feminist deconstruction. Since her work is a critique of the philosophical critique of the Enlightenment, one can identify traces , today almost forgotten, of a feminist tradition of thought which can be considered as a discourse of emancipation. Furthermore, this critical exercise becomes an intellectual and social non-patriarchal project of a society free from gender restrictions. In this sense, Celia Amoros’ philosophical work develops into philosophical feminism, not only in terms of being critical revision of the history of ideas, but also and principally because it takes shape as critical reflection and as direct dialogue with present-day philosophical discourse.
Keywords: Deconstruction; Sexual difference; Gender; Equality; Enlightenment; Patriarchy; Sex/gender system